Enhanced Antioxidant Activity and Secondary Metabolite Production in Tartary Buckwheat under Polyethylene Glycol (PEG)-Induced Drought Stress during Germination - Md. Shakhawat Hossain; Jing Li; Chenyang Wang; Fakhrul Islam Monshi; Rehenuma Tabassum; Md Ashraful Islam; Muhiuddin Faruquee; Md. Abdul Muktadir; Md Sultan Mia; A. K. M. Mominul Islam; Ahmed Khairul Hasan; Ashim Sikdar; et al. (Agronomy, 2024)
Drought stress is one of the key factors impeding agricultural productivity worldwide. This experiment aimed at investigating the polyethylene glycol (PEG)-induced drought stress effects on seed germination, physiology, and biochemical mechanisms in Tartary buckwheat genotypes. Four PEG-induced stress conditions (0%, 10%, 20%, and 30%) were applied to 14 selected genotypes at the germination stage to evaluate their stress tolerance capacity. Significant differences were obtained in germination percentage, relative water content (RWC), and all growth parameters among the studied 14 genotypes. Based on the stress tolerance index (STI), XiNong 9943, XiNong 9940, and QianKu-5 were found to be tolerant, and QuanKu-4 was susceptible. These cultivars were selected for further physiological and biochemical characterization. The results demonstrated that the activity of enzymes was significantly increased with the increase in PEG dose. SOD (superoxide dismutase), POD (peroxidase), CAT (catalase), and APX (ascorbate peroxidase) levels obtained at 30% PEG in the XiNong 9943 genotype were 2.01, 2.19, 4.92, and 4.46 times higher, respectively, than the normal growth condition (T0). Moreover, the secondary metabolite content also increased with the increase in PEG dose. At 30% PEG, the genotype XiNong 9943 yielded phenols, flavonoids, polyphenol oxidase (PPO), and phenylalanine ammonia lyase (PAL) levels that were higher by 131%, 95%, 154%, and 164%, respectively, than T0 condition. From both the findings of the activity of enzymes and the secondary metabolite content, the genotypic response to drought was ranked in the following order: XiNong 9943 > XiNong 9940 > QianKu-5 > QianKu-4, which supported the STI selection system. Assessing the overall performance, the genotype XiNong 9943 shows drought tolerance, which can be useful material for future buckwheat breeding programs.